Nutritional status classification of preschoolers enrolled in a public and private school in the city of Pelotas-RS - Silva, Luisa Silveira da (2022)
Objective: To describe the nutritional status of preschoolers matriculated in two schools of children education, according to demographic characteristics and the type of school. Materials and Methods: cross sectional study including preschoolers between the ages of three and six years old matriculated in two schools, being one public and one private. The data collection was conducted in the schools and the anthropometry according to the Food and Nutrition Surveillance System technical rules and the classification of nutritional status by the growth curves adopted by the World Health Organization 2006-2007. Descriptive analyses were conducted and prevalence of overweight, obesity and stunting were calculated according to sex, child’s age and the type of school. Results: 270 children were analyzed, 23,0% presented overweight, 7,0% obesity and 2,6% stunted. Children of the public school presented higher prevalences of overweight, obesity and height déficit, however, did not have significant statistical difference. The overweight prevalence was higher in children aged five or over when compared with younger children (p<0,001) and the prevalence of obesity increased in according to the child’s age. Discussion: Contrary to results from other studies, the preschoolers of public school had a higher prevalence of overweight and obesity higher than private school preschoolers. Conclusions: There was elevated prevalence of overweight and obesity, especially between the older children.